If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 4) + 3 = 9x + 5(x + 3) Reorder the terms: 5(4 + x) + 3 = 9x + 5(x + 3) (4 * 5 + x * 5) + 3 = 9x + 5(x + 3) (20 + 5x) + 3 = 9x + 5(x + 3) Reorder the terms: 20 + 3 + 5x = 9x + 5(x + 3) Combine like terms: 20 + 3 = 23 23 + 5x = 9x + 5(x + 3) Reorder the terms: 23 + 5x = 9x + 5(3 + x) 23 + 5x = 9x + (3 * 5 + x * 5) 23 + 5x = 9x + (15 + 5x) Reorder the terms: 23 + 5x = 15 + 9x + 5x Combine like terms: 9x + 5x = 14x 23 + 5x = 15 + 14x Solving 23 + 5x = 15 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 23 + 5x + -14x = 15 + 14x + -14x Combine like terms: 5x + -14x = -9x 23 + -9x = 15 + 14x + -14x Combine like terms: 14x + -14x = 0 23 + -9x = 15 + 0 23 + -9x = 15 Add '-23' to each side of the equation. 23 + -23 + -9x = 15 + -23 Combine like terms: 23 + -23 = 0 0 + -9x = 15 + -23 -9x = 15 + -23 Combine like terms: 15 + -23 = -8 -9x = -8 Divide each side by '-9'. x = 0.8888888889 Simplifying x = 0.8888888889
| 8n=7(2n+7) | | 1-6(-2x-6)=109 | | R^2+12r-66=-6 | | -4/7=?/28 | | ln(7x)=81 | | (X+2)-4-6x=3x+10 | | 91=-7(7-4k) | | 14=z-y | | -5n-7=23 | | Cosx=2sinx | | -6-6x=1x+4 | | 14a^2+7a-196=0 | | 355=-5n-5(8n-8) | | 2cos^2x+5sinx-5=0 | | 1/9=?/45 | | (X+2)-2(4-3x)=2(x+4)-4 | | (-7)-x=-5 | | 9n^2+94n-168=0 | | 7x-8=55-2x | | (-3)-x=2 | | p-12=218 | | .5x^2=8 | | -6a=36a | | y=2x-5x+7 | | 2.9r=-5.7t-5 | | x-(-14)=-11 | | 5y-9=7+y | | 60-what+10=20 | | 5=1-4(-5) | | 3m-7=m-13 | | 3x+9x+5=17 | | 4-5p=8 |